New species and new records in Roccellaceae (Arthoniales) from the Andaman Islands, India - Jagadeesh Ram, Tam (Phytotaxa, 2014)
Four new species in Roccellaceae: Bactrospora littoralis, B. medians, Chiodecton andamanicum and Sagenidiopsis atroalba are described from the Andaman Islands, India. Bactrospora littoralis has acicular, 7-septate Patellarioides-type ascospores whereas B. medians has biclavate, 15–24-septate, Homalotropa-type ascospores. Chiodecton andamanicum has much small ascomata, thin, hyaline to pale brown hypothecium and 4–5-septate ascospores. Sagenidiopsis atroalba has a byssoid thallus with white prothallus, dark brown to blackish hypothallus and smaller ascomata, asci and ascospores. Bactrospora carolinensis (Ellis & Everh.) R.C. Harris, Opegrapha apomelana A. Massal., O. dekeselii Ertz, O. irosina Vain. and O. robusta Vain. are reported as new records for India.